Resuscitation of patients with cardiac arrest by ambulance staff with extended training in West Yorkshire. Issue 6752 (22nd September 1990) - Wright, D; Bannister, J; Ryder, M; Mackintosh, A F
Abstract : OBJECTIVE--To investigate the results of resuscitation of patients with cardiac arrest by ambulance staff with extended training in West Yorkshire. DESIGN--Study of all such attempts at resuscitation over 32 months, based on the standard report form for each call made by the ambulance staff and the electrocardiogram that showed the initial rhythm in each patient. SETTING--Area covered by West Yorkshire ambulance service. SUBJECTS--1196 Patients with cardiac arrests attended by 29 ambulance staff with extended training. MAIN OUTCOME MEASURE--Result of resuscitation. RESULTS--The initial rhythm was asystole or electromechanical dissociation in 740 patients and ventricular fibrillation in 456 patients; overall 65 patients survived to be discharged from hospital. Sixty four of the 456 patients in whom ventricular fibrillation was the initial rhythm recorded, and 46 in whom ventricular fibrillation persisted after the ambulance staff arrived, survived. Only one of the 740 patients who initially had asystole or electromechanical dissociation survived. Factors associated with a greater chance of ventricular fibrillation occurring were: age less than 71, the arrest being witnessed by a bystander, resuscitation by a bystander, the arrest occurring in a public place, and a response time by the ambulance staff of less than six minutes. For patients found in ventricular fibrillation a shorter response time was associated with improved survival but resuscitation by a bystander was not. Additional skills learnt during extended training were used for 51 of the 65 patients who survived. CONCLUSIONS--Ambulance staff with extended training can save the lives of patients with cardiac arrest due to fibrillation, though asystole and electromechanical dissociation have a poor prognosis and should perhaps receive little attention during extended training.